Evaluation of fixed and variable hospital costs due to Clostridium difficile infection: institutional incentives and directions for future research. Issue 4 (April 2017) - Ryan, P.; Skally, M.; Duffy, F.; Farrelly, M.; Gaughan, L.; Flood, P.; McFadden, E.; Fitzpatrick, F.
Summary: Background: Economic analysis of Clostridium difficile infection (CDI) should consider the incentives facing institutional decision-makers. To avoid overstating the financial benefits of infection prevention, fixed and variable costs should be distinguished. Aim: To quantify CDI fixed and variable costs in a tertiary referral hospital during August 2015. Methods: A micro-costing analysis estimated CDI costs per patient, including the additional costs of a CDI outbreak. Resource use was quantified after review of patient charts, pharmacy data, administrative resource input, and records of salary and cleaning/decontamination expenditure. Findings: The incremental cost of CDI was €75, 680 (mean: €5, 820 per patient) with key cost drivers being cleaning, pharmaceuticals, and length of stay (LOS). Additional LOS ranged from 1.75 to 22.55 days. For seven patients involved in a CDI outbreak, excluding the value of the 58 lost bed-days (€34, 585); costs were 30% higher (€7, 589 per patient). Therefore, total spending on CDI was €88, 062 (mean: €6, 773 across all patients). Potential savings from variable costs were €1, 026 (17%) or €1, 768 (26%) if outbreak costs were included. Investment in an antimicrobial pharmacist would require 47 CDI cases to be prevented annually. Prevention of 5%, 10% and 20% CDI would reduce attributable costs by €4, 403, €8, 806 and €17, 612. Increasing the incremental LOS attributable to CDI to seven days per patient would have increased costs to €7, 478 or €8, 431 (if outbreak costs were included). Conclusion: As much CDI costs are fixed, potential savings from infection prevention are limited. Future analysis must consider more effectively this distinction and its impact on institutional decision-making.